The Changing Age of Individuals Seeking Presymptomatic Genetic Testing for Huntington Disease. Issue 5 (20th February 2018) - Holman, Melissa A.; Quillin, John; York, Timothy P.; Testa, Claudia M.; Rosen, Ami R.; Norris, Virginia W.
Abstract: Huntington disease (HD) is a progressive neurodegenerative disorder. Presymptomatic genetic testing allows at‐risk individuals to clarify their risk status. Understanding the characteristics and motivations of individuals seeking HD presymptomatic genetic testing better equips genetic counselors and other healthcare professionals to provide comprehensive and personalized care. The aims of this study were to (1) determine whether the average age when individuals seek presymptomatic HD genetic testing has decreased over time, (2) assess motivations for seeking testing, (3) explore whether there is a relationship between age and motivations, and (4) explore genetic counselors' perceptions of the shift in age. Data from the US HD testing centers ( N  = 4) were analyzed. A small but statistically significant decrease in age of individuals seeking presymptomatic testing was observed ( p  = 0.045). HD community members ( N  = 77) were surveyed regarding presymptomatic testing motivations. Younger individuals were more likely than older individuals to cite "To learn whether or not you would develop HD" and "To make choices about further education or a career" compared to older individuals ( p  < 0.05). Conversely, older individuals more frequently cited "To give children a better idea of their risk" ( p  < 0.002). Sixteen percent of genetic counselors surveyed (6/37) perceived a change in age of testing. All of these respondents had provided HD testing for ten or more years and anecdotally believed the age at testing has decreased over time. Study results help providers personalize counseling based on patient's age and serve as a starting point for more research into the relationship between age at testing and motivations for testing.